Contextual effects of mesenchymal stem cell injections for knee osteoarthritis: systematic review and meta-analysis of randomized controlled trials - Yin, Fengsheng; Wu, Houdong; Tong, Dan; Luo, Gan; Deng, Zhen; Yan, Qinyi; Zhang, Yu (Frontiers in Medicine, 2025)
PurposeTo quantify the proportion of the overall clinical improvement produced by intra-articular mesenchymal stem cell (MSC) injections for knee osteoarthritis (KOA) that is attributable to contextual (placebo-related) effects.MethodsThis PRISMA-compliant systematic review and meta-analysis (PROSPERO CRD420251026818) searched five databases (CENTRAL, Embase, MEDLINE, Web of Science and Scopus) to 24 March 2025. Randomized controlled trials enrolling adults with KOA that compared MSC injections with inert placebo were included. Primary outcome was change in pain intensity (VAS or WOMAC-pain); physical function was analysed secondarily. Two reviewers independently extracted data and assessed risk of bias. The proportion of the treatment effect attributable to contextual factors (PCE) was calculated as described by Tsutsumi et al. Pain and function outcomes at 6 and 12 months were pooled with inverse-variance random-effects meta-analysis, and evidence certainty was appraised using GRADE.ResultsEight RCTs (467 patients) met the inclusion criteria. At 6 months, contextual factors accounted for approximately 63% of pain reduction and 61% of functional improvement, with low heterogeneity (I2 ≤ 8%). At 12 months, contextual factors explained ~50% of pain relief and ~66% of functional gains, again with very low heterogeneity (I2 = 0%). Certainty of evidence was rated low for both time-points (GRADE).ConclusionBased on low-certainty evidence, this meta-analysis suggests that in knee osteoarthritis the majority of symptomatic improvement following intra-articular MSC injections is attributable to contextual (placebo) effects, whereas the MSCs themselves confer only a modest incremental benefit.Systematic review registrationCRD4-2025-1636181, https://www.crd.york.ac.uk/PROSPERO/view/CRD420251026818.